Inverse synthetic aperture radar imaging with MATLAB algorithms : with advanced sar/isar imaging concepts, algorithms, and matlab codes - Özdemir, Caner (Wiley series in microwave and optical engineering., 2021)
"This book is an updated edition covering in greater detail the fundamentals of inverse synthetic aperture radar (ISAR). Theoretical as well as practical aspects of ISAR are presented and illustrative examples are used to describe the signal processing algorithms used for ISAR imaging. The topics presented in each chapter are supported by MATLAB codes to assist the users in better understanding the ISAR imaging principles. This edition includes discussions of new topics related to ISAR imaging and describes hardware design for ISAR"--